Regulation of myelin genes implicated in psychiatric disorders by functional activity in axons - Lee, Philip R.; Fields, Douglas (Frontiers in Neuroanatomy, 2009)
Myelination is a highly dynamic process that continues well into adulthood in humans. Several recent gene expression studies have found abnormal expression of genes involved in myelination in the prefrontal cortex of brains from patients with schizophrenia and other psychiatric illnesses. Defects in myelination could contribute to the pathophysiology of psychiatric illness by impairing information processing as a consequence of altered impulse conduction velocity and synchrony between cortical regions carrying out higher level cognitive functions. Myelination can be altered by impulse activity in axons and by environmental experience. Psychiatric illness is treated by psychotherapy, behavioral modification, and drugs affecting neurotransmission, raising the possibility that myelinating glia may not only contribute to such disorders, but that activity-dependent effects on myelinating glia could provide one of the cellular mechanisms contributing to the therapeutic effects of these treatments. This review examines evidence showing that genes and gene networks important for myelination can be regulated by functional activity in axons.